2-Azido-1-(4-nitrophenyl)ethanone - Yousuf, Sammer (International Union of Crystallography, 2012)
In the title compound, C(8)H(6)N(4)O(3), the ketone [C—C(=O)—C] and nitro groups are tilted with respect to the benzene ring by 18.92 (6) and 24.11 (15)°, respectively. In the crystal, molecules are linked into interwoven chains running parallel to the [100] direction by C—H⋯N hydrogen bonds and weak π–π stacking interactions, with centroid–centroid separations of 3.897 (3) Å.